Messenger RNAs that are not synthesized by RNA polymerase II can be 3' end cleaved and polyadenylated. - Fodor, E; Mikulasova, A; Mingay, L; Poon, L; Brownlee, G (2000)
The poly(A) tail of influenza virus mRNAs is synthesized by the viral RNA polymerase by reiterative copying of a U5-7 sequence near the 5' end of the viral RNA (vRNA) template. We have engineered a vRNA molecule by replacing its viral U6 poly(A) site with a negative-sense eukaryotic polyadenylation signal. The vRNA was transcribed by the viral RNA polymerase and the transcription product was processed by the cellular 3' end processing machinery in vivo. According to the current model, 3' end processing of eukaryotic pre-mRNAs is coupled to cellular RNA polymerase II (pol II) transcription; thus only RNAs synthesized by pol III are believed to be polyadenylated efficiently. Our results show that the cellular polyadenylation machinery is nevertheless able to recognize and process RNA transcripts that are not synthesized by pol II, indicating that synthesis by pol II is not an absolute requirement for 3' end processing in vivo.